2023
DOI: 10.1021/acs.jcim.2c01597
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at Ser289 Enhances the Oligomerization of Tau Repeat R2

Abstract: In tauopathies such as Alzheimer's disease (AD), aberrant phosphorylation causes the dissociation of tau proteins from microtubules. The dissociated tau then aggregates into sequent forms from soluble oligomers to paired helical filaments and insoluble neurofibrillary tangles (NFTs). NFTs is a hallmark of AD, while oligomers are found to be the most toxic form of the tau aggregates. Therefore, understanding tau oligomerization with regard to abnormal phosphorylation is important for the therapeutic development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…By performing 500 ns REMD simulation with the Charmm36m force field, Man et al investigated the effect of phosphorylated Ser289 on dimeric structures of tau R2 peptides and reported that the βsheet probability of the R2 dimer was 14.17% and phosphorylation increased the β-sheet content to 16.89%. 59 This different result of β-sheet probability of the R2 dimer may be due to the different force fields used in our and Man et al's works. The probability of the β-strand length of the R2 dimer in two systems is shown in Figure 3c.…”
Section: K280 Acetylation Promotes the Aggregation Of R2 Peptides By ...mentioning
confidence: 69%
See 2 more Smart Citations
“…By performing 500 ns REMD simulation with the Charmm36m force field, Man et al investigated the effect of phosphorylated Ser289 on dimeric structures of tau R2 peptides and reported that the βsheet probability of the R2 dimer was 14.17% and phosphorylation increased the β-sheet content to 16.89%. 59 This different result of β-sheet probability of the R2 dimer may be due to the different force fields used in our and Man et al's works. The probability of the β-strand length of the R2 dimer in two systems is shown in Figure 3c.…”
Section: K280 Acetylation Promotes the Aggregation Of R2 Peptides By ...mentioning
confidence: 69%
“…It is noted that PHF6* ( 275 VQIINK 280 ) is one of the fibril-nucleating core motifs of tau and plays a vital role in tau aggregation; , thus, the enhanced β-sheet probability in this region is supposed to promote tau dimerization. By performing 500 ns REMD simulation with the Charmm36m force field, Man et al investigated the effect of phosphorylated Ser289 on dimeric structures of tau R2 peptides and reported that the β-sheet probability of the R2 dimer was 14.17% and phosphorylation increased the β-sheet content to 16.89% . This different result of β-sheet probability of the R2 dimer may be due to the different force fields used in our and Man et al’s works.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermolecular 2P-collabs were also observed by Man et al when modeling a system comprising two monophosphorylated (pSer289) tau-R2 fragments with the C36 FF. 69 A pS289-Na + -pS289 bridge was present in 16% of the MD trajectory, and this result raises the question of whether nP-collabs could be a possible pathway to aggregation by bridging monomers. Generally speaking, all these recognized and unrecognized sightings of nP-collabs make a strong case for the importance of bulk ions in MD simulations, and we therefore urge the computational community to reconsider their relevance and keep track of them in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Tau, as a 'tubulin-associated unit' and a protein constituting over 80% of MT-associated proteins, primarily plays a physiological role in bundling and stabilizing axonal MTs through tubulin polymerization, a process that is disrupted by phosphorylation [63][64][65]. Additionally, phosphorylation, particularly by GSK-3β, results in reduced tau transport along the axon due to diminished interaction with kinesin [64,66].…”
Section: From Tau Phosphorylation To Neurofibrillary Tangle Formationmentioning
confidence: 99%